PENGUKURAN KINERJA NON FINANSIAL DALAM MENINGKATKAN KINERJA FINANSIAL : STUDY LITERATUR - Basri, Yesi Mutia (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This paper is a study literature concerning non-finansial measures for financialperformance purposes. Its purpose is making a literature review concerning the useof non-financial performance for performance measures and relation non financialperformance on financial performance. The literature review is related to (a)limitations of finansial measures; (b) the reason of used nonfinancial performance(c) benefit non financial measure (d) privious research in non financial performanceand financial performance.Key Words: Non-financial measures, non-financial information, performancemeasures.